Використання індексу фрактальності для оцінки ефективності складних фінансово-економічних систем - Соловйов, В.М.; Стратійчук, І.О. (Культура народов Причерноморья, 2013)
У статті розглянута методика побудови індексу фрактальності на основі
мультимасштабної ентропії шаблонів для оцінки ефективності складних фінансово-економічних
систем, представлені результати експериментальної роботи з ранжування світових банків за
ефективністю. Показано, що найбільш ефективними є Barclays PLC та BNP Paribas, найменш -
UniCredit S.p.A. і China Construction Bank Corporation. Серед індексів фондових ринків більшу
ефективність показали ftse (Англія), aex (Нідерланди), dax (Німеччина), меншу - iseq (Ірландія), jkse
(Індонезія), bvsp (Бразилія). В статье рассмотрена методика построения индекса фрактальности на основе
мультимасштабной энтропии шаблонов для оценки эффективности сложных финансово-экономических
систем, представлены результаты экспериментальной работы по ранжированию мировых банков по
эффективности. Показано, что наиболее эффективными являются Barclays PLC и BNP Paribas,
наименее - UniCredit S.p.A. и China Construction Bank Corporation. Среди индексов фондовых рынков
большую эффективность показали ftse (Англия), aex (Голландия), dax (Германия), меньшую - iseq
(Ирландия), jkse (Индонезия), bvsp (Бразилия). The method of calculation index of fractality based on multiscale sample entropy for evaluation of
complex and economic efficiency, results of experimental work of world banks efficiency ranking were shown in
this paper. Shown that the highest efficiency have Barclays PLC and BNP Paribas, lowest - UniCredit S.p.A. and
China Construction Bank Corporation. The highest efficiency have ftse (England), aex (Netherlands), dax
(Germany), lowest - iseq (Ireland), jkse (Indonesia), bvsp (Brazil) among the shown stock market indices.
This paper research allowed to develop and test a new experimental methodologies to evaluate efficiency of
complex financial and economic systems. The algorithm which based on the fractal index is universal because it
can be used with different levels of complexity and input data.
Research is based on the definition of a complex system as such, where measure of efficiency depends on
fractality of its dynamics. This approach provides possibility of high correlation behavior between different
market participants on different scales. Accordingly, if such correlation is not present, then the system is defined
as an inefficient. Using normalized values from the first to the last scales to calculate the index of fractality as a
measure of complexity. Overall this index is universal because can be calculate on any measure. In this paper
we use multiscale sample entropy to calculate index of fractality for world banks.